The Effect ofLearning Model on Everyone Is A Teacher Here Sociology Learning Outcomes in Class XI Students of SMA Negeri 3 Buru Selatan - Koce Y. Solissa; Lambertus J. Lokollo; J. L Kundre (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study was to determine the effect of thelearning model everyone is a teacher here on the learning outcomes of sociology in class XI students of SMA Negeri 3 Buru Selatan. The type of research used in this study is a quasi-experimental or (research quasi-experimental). The results showed that there was a significant influence between the learning outcomes of sociology before and after the use of thelearning model for the everyone is a teacher here XI grade students of SMA Negeri 3 Buru Selatan